Multiwavelength investigation of extended green object G19.88-0.53: revealing a protocluster. Issue 4 (5th August 2020) - Issac, Namitha; Tej, Anandmayee; Liu, Tie; Varricatt, Watson; Vig, Sarita; Ishwara Chandra, C H; Schultheis, Mathias; Nandakumar, Govind
ABSTRACT: A multiwavelength analysis of star formation associated with the extended green object, G19.88-0.53 is presented in this paper. With multiple detected radio and millimetre components, G19.88-0.53 unveils as harbouring a protocluster rather than a single massive young stellar object. We detect an ionized thermal jet using the upgraded Giant Meterwave Radio Telescope, India, which is found to be associated with a massive, dense and hot ALMA 2.7 mm core driving a bipolar CO outflow. Near-infrared spectroscopy with UKIRT–UIST shows the presence of multiple shock-excited H2 lines concurrent with the nature of this region. Detailed investigation of the gas kinematics using ALMA data reveals G19.88-0.53 as an active protocluster with high-mass star-forming components spanning a wide evolutionary spectrum from hot cores in accretion phase to cores driving multiple outflows to possible UCH ii regions.